Students’ Problems in Learning Speaking Skills (A Case Study Atsma Negeri 1 Panyabungan Selatan) - Tamara, Indah; Siregar, Ayu Meita Puteri; Yahsya, Akhrif (MUDABBIR Journal Research and Education Studies, 2025)
This research aims to identify the problems faced by students during the process of learning English speaking skills at SMA Negeri 1 Panyabungan Selatan and to find out why the problems students face become factors that hinder their English speaking ability at SMA Negeri 1 Panyabungan Selatan, specifically focusing on 12th-grade students in MIA II. The study employs a qualitative descriptive method, emphasizing the interpretation of events and the acquisition of real data to depict the actual conditions experienced by students. Primary data were collected through questionnaires and observations, focusing on the challenges students encounter in mastering English speaking skills, including low vocabulary mastery, grammatical barriers, pronunciation issues, shyness, nervousness, fear of making mistakes, lack of confidence, limited practice, the dominance of the mother tongue, and low motivation. This research was conducted over four sessions at SMA Negeri 1 Panyabungan Selatan, focusing on the MIA II class, involving 20 students, from August 30, 2024, to September 30, 2024. The findings reveal that the English-speaking skills of the 12th-grade MIA II students remain at a low level. While some students demonstrated better speaking skills, the majority struggled to express themselves in English. In-depth classroom and outside observations showed that most students were unable to convey their thoughts effectively in English. Several factors hinder students' ability to speak English effectively. A primary issue is low vocabulary mastery, which makes it difficult for students to form simple sentences and leads to struggles in finding the right words and uncertainty about pronunciation. Many students also lack a solid understanding of English grammar, resulting in frequent errors that disrupt communication and diminish their confidence. Difficulties with pronunciation further discourage participation in speaking activities due to fear of mistakes or ridicule. Additionally, limited practice, as students focus more on written tasks and rely heavily on their mother tongue in the classroom, reduces their opportunities to practice English. Lastly, low motivation affects their progress, as many students show little interest in improving their speaking skills or understanding the relevance of English proficiency. Collectively, these factors significantly limit their overall progress in speaking English fluently.